Student Information Management System : A Case Study of Sekolah Menengah Kebangsaan Seri Mahkota - Badru Duja Khan, Saruvari (2005)
Every aspect of management relies on information to succeed. Information has become a critical resource to organisations and individuals and should be properly managed to ensure its cost effective use. To improve the performance of the organisation, the management must be economical, efficient and effective. Information systems and organisations have been highly interconnected with each other. The development and the use of an information management system (MIS) leads to better planning, better decision-making and better results. This study was carried out in order to produce a prototype for Sekolah Menengah Kebangsaan Seri Mahkota Student Information Management System (SeriSPMP). The development of the web-based prototype would be able to replace the traditional way of managing student information, where this traditional way places a heavy burden on the teachers and school administrators. This prototype was developed as a working prototype where is can be enhanced in the future. The system development was designed using the Database Application Life Cycle (DBALC) approach.